The Effect of Working Environment, Leadership and Organizational Culture on Law Enforcement Officers’ Performance: The case of Police Resort at Musi Rawas Regency - Harsono, Harsono; Asiati, Diah Isnaini; Choiriyah, choiriyah (International Journal of Business, Management and Economics, 2025)
This research aims to determine the influence of the work environment, leadership, and organizational culture on the performance of Musi Rawas Resort Police Members. This type of research is associative; the variables used in this research are work environment, leadership, and organizational culture. The objects of this research are all members of the Musi Rawas Police Department. The population in this study consisted of 188 members, and the sample size was determined using the Slovin formula with a 5% error rate, resulting in a total sample of 128 members. The sampling method used was cluster sampling. The primary data used in this research were collected through a questionnaire. The analysis technique employed is multiple linear regression, utilizing the SPSS application. The research results demonstrate that 1) the work environment, leadership, and organizational culture have a positive and significant influence on the performance of members of the Musi Rawas Resort Police. 2) The work environment has a positive and significant influence on the performance of members of the Musi Rawas Resort Police. 3) Leadership has a positive and significant influence on the performance of members of the Musi Rawas Resort Police. 4) Organizational culture has a positive and significant influence on the performance of members of the Musi Rawas Resort Police. The coefficient of determination obtained indicates that the work environment, leadership, and organizational culture contribute 69.5% to performance; the remaining 30.5% is influenced by other variables not studied